1996
DOI: 10.1111/j.1467-8624.1996.tb01884.x
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Domain-Specific Knowledge and Domain-General Discovery Strategies: A Study with Sinking Objects

Abstract: Recent work on scientific reasoning has largely focused on either domain-specific content knowledge or domain-general reasoning knowledge. This study investigated the interaction between the 2 types of knowledge in a real-world domain in which strict control of variables was not possible. We used a context, sinking objects, in which 10-, 12-, and, 14-year-old children's strong a priori beliefs could be revealed by participant-designed experiments. The results showed that most children initially believed weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 32 publications
2
53
0
Order By: Relevance
“…First, adolescents' inaccurate knowledge in physical science is typically robust e meaning their knowledge structures have been consistently reinforced and are most likely difficult to change (Brna, 1987;Chinn & Malhotra, 2002;Clement, 1982;Penner & Klahr, 1996). For example, in previous research, most early adolescents inaccurately reported that the mass of an object affects the speed at which it travels and were unlikely to change their response, even when provided contrary data (Renken & Nunez, 2010).…”
Section: Adolescents' Understanding Of Science Conceptsmentioning
confidence: 93%
“…First, adolescents' inaccurate knowledge in physical science is typically robust e meaning their knowledge structures have been consistently reinforced and are most likely difficult to change (Brna, 1987;Chinn & Malhotra, 2002;Clement, 1982;Penner & Klahr, 1996). For example, in previous research, most early adolescents inaccurately reported that the mass of an object affects the speed at which it travels and were unlikely to change their response, even when provided contrary data (Renken & Nunez, 2010).…”
Section: Adolescents' Understanding Of Science Conceptsmentioning
confidence: 93%
“…Of course, sometimes their beliefs are mistaken; they hold misconceptions. For example, children believe that heavy stuff sinks fast (e.g., Kloos & Somerville, 2001;Penner & Klahr, 1996), that the sun is alive, but not plants (Venville, 2004), or that the earth is disc-shaped (e.g., Vosniadou & Brewer, 1992). To what extent can early science instruction build upon children's existing knowledge to convey new facts and change mistaken beliefs?…”
Section: Can Preschoolers Learn About Scientific Facts?mentioning
confidence: 99%
“…Thus, this latter line of investigation focused on scientific reasoning processes involved in acquiring new knowledge starting with prior knowledge as a point of departure. Investigating the development of scientific reasoning or thinking under this umbrella has been referred to as a "domain-specific" (Penner & Klahr, 1996;Zimmerman 2000), "knowledge-based" (Samarapungavan, 1992) or "conceptual change" (Schauble, 1996) approach. A second major approach to the study of scientific reasoning deals with processes involved in hypothesis testing and experimental design (e.g., Kuhn et al, 1988;Lawson et al, 2000;Schunn & Anderson, 1999) and has been referred to as a "domaingeneral" approach (Penner & Klahr, 1996) or "experimentation strategy" (Schauble, 1996).…”
Section: Framework For Studying Scientific Reasoningmentioning
confidence: 99%
“…Some researchers (e.g., Penner & Klahr, 1996;Schunn & Anderson, 1999) view these connotations of scientific reasoning as reflecting two types of knowledge, declarative and procedural. Declarative knowledge is descriptive or substantive knowledge (i.e., knowing that), whereas procedural knowledge is performative knowledge that is enacted in the form of skills (i.e., knowing how) (Schunn & Anderson, 1999).…”
Section: Framework For Studying Scientific Reasoningmentioning
confidence: 99%